Sikap Kepemimpinan Wirausahawan Millenial dalam Perspektif Chief Executive Officer (CEO) Millenial - Monalisa Monalisa; Muhammad Akhyar; Musa Pelu (Universitas Sebelas Maret, 2022)
Being a millennial entrepreneur who serves as a professional CEO, despite his young age as a millennial generation, there are several main approaches to leadership that need to be done by a millennial CEO that is seen from the point of view of millennial netizens. So how millennial entrepreneurs have a leadership attitude to become a millennial CEO who can increase professional value among relationships, customers and the wider community. The method used in this study is case studies with qualitative approaches. The type of data used is primary data through instagram social media surveys to see the activities of millennial entrepreneurs who reflect the leadership attitude of a millennial CEO. The sample of concern is CEO Indra Kesuma, a millennial entrepreneur from the field with his business instagram account kursustrading.id, action.kindness and others. And Esther Nathalia who became the CEO of millennials of my produktifkuy Instagram account. The results of the research findings are that millennial entrepreneurs with ceo positions in their businesses, have an advanced leadership attitude. Millennial CEOs are hardworking, resilient, responsible, and still care about the people below by helping and helping them both help in the form of money, open jobs and provide very useful knowledge through instagram content shared. In conclusion, although millennials are considered a vulnerable generation of despair, they show their own value through their leadership attitude in developing their entrepreneurship.